Prispevek k poznavanju opraševalcev vrst Euphorbia nicaeensis All. in E. lucida W. and K. - Frajman, Božo (Natura Sloveniae, 2001)
The composition of inflorescence visitors of two Euphorbia species is presented and their role as possible pollinators is discussed. Pollinators of Euphorbia nicaeensis were studied in the Slovene Karst, near Sežana, and pollinators of E. iucida on the plants growing on the shores of the intermittent Lake Cerknica (both SW Slovenia) in the middle of June 2000. The comparison between abundance of different animals (especially insects) visiting both Euphorbias is presented.
Keywords: Cvetni prah; Entomologija; Entomology; Insects; Insekti; Plants; Pollen; Rastline